Randomized Clinical Trial Comparing Botulinum Toxin Injection with Nitroglycerine Ointment for Treatment of Chronic Anal Fissure - Timilsina, Binaya; Agarwal, C.S.; Adhikari, S.; Agrawal, S.; Gupta, R.K. (Journal of BP Koirala Institute of Health Sciences, 2018)
Background and Objectives: Although surgery is the gold standard treatment for anal fissure, the main concern remains its side effects and complications in terms of permanent incontinence. In recent years, treatment of chronic anal fissure has shifted from surgical to medical. This study compares the efficacy and safety of two non-surgical treatments- botulinum toxin (BTX) injection with nitroglycerine (NTG) ointment for the treatment of chronic anal fissure. Methods: One hundred and twelve adults were assigned randomly to receive treatment with either type A botulinum toxin (15 units) injected into internal anal sphincter or 0.2% nitroglycerine ointment applied thrice daily for 8 weeks. Results: After 2 months, the fissures were healed in 50 (89.3%) of 56 patients in botulinum toxin group and in 39 (69.6%) of 56 patients in nitroglycerine group (P= 0.01). Seventeen (23%) patients in nitroglycerine group complained of headache while none of the patients in botulinum toxin group had any forms of adverse effects. The recurrence rate of nitroglycerine group was higher than botulinum toxin group at 3 months (4.3% in BTX vs 16.7% in NTG, P = 0.057) and at 6 months (8.5% in BTX vs 36.1% in NTG, P = 0.002). Conclusion: Although treatment with either topical nitroglycerine or botulinum toxin is effective as an alternative to surgery for patients with chronic anal fissure, botulinum toxin is the more effective option.